SOSIALISASI PENCEGAHAN PERNIKAHAN USIA DINI SEBAGAI UPAYA MENINGKATKAN KESADARAN REMAJA DI DESA TUBO SELATAN KABUPATEN MAMUJU PROVINSI SULAWESI BARAT - Jeffriansyah Dwisahputra Amori; Indriani, Indriani; Mu’fidatul Nurul Hajjad; Abdul Wahab; Rhena, Rhena (Bajang Institute, 2025)
Early marriage remains a serious social problem in various regions in Indonesia, including South Tubo Village. This practice often results in school dropout, reproductive health risks, and a low quality of life, especially for adolescent girls. This community service activity aims to raise awareness among adolescents and parents about the negative impacts of early marriage and the importance of continuing education. The method used was a participatory approach and interactive outreach that directly involved adolescents and their families. The results of the activity showed a significant increase in participants' understanding of the risks of early marriage and a growing community commitment to preventing the practice. The formation of the Marriage Age Awareness Youth Forum is one of the sustainable outcomes of this program. This activity can be used as a model for community-based social education that can be replicated in other rural areas, particularly in West Sulawesi. Strengthening cross-sector collaboration and community empowerment are key to long-term prevention of child marriage.